'Acceptable rebellion': marketing hipster aesthetics to sell Camel cigarettes in the US. Issue 3 (25th May 2010) - Hendlin, Yogi; Anderson, Stacey J; Glantz, Stanton A
Abstract : Objective: The aim of the present work was to understand why and how RJ Reynolds and other tobacco companies have marketed tobacco products to young adult social trendsetting consumers (termed 'hipsters') to recruit trendsetters and average consumers to smoke. Methods: Analysis of tobacco industry documents and industry marketing materials. Results: Since 1995, RJ Reynolds developed its marketing campaigns to better suit the lifestyle, image identity and attitudes of hip trendsetters (so-called 'hipsters'), and Camel's brand identity actively shifted to more closely convey the hipster persona. Camel emphasised in-venue events such as promotional music tours to link the brand and smoking to activities and symbols appealing to hipsters and their emulating masses. Conclusions: To reach this targeted and socially valuable trend-setting population, public health advocates must tap into hipster psychology and expose to the targeted community the tobacco company's efforts to infiltrate the hipster community to turn hipsters into tobacco-using role models.